Controlled or automatic? Influence of congruency proportion and stimulus-onset asynchrony on the brightness-valence and spatial-valence metaphoric congruency effects. Issue 6 (June 2022) - Huang, Yanli; Tse, Chi-Shing; Xie, Jiushu; Shen, Manqiong; Wang, Ruiming
Whether a cognitive process is operated automatically or in a controlled manner has been a long-standing question in cognitive psychology. However, this issue has not been investigated in the activation of metaphoric association. A primed word valence judgement task is often used to test the activation of metaphoric association, in which participants first see a prime (bright/dark square or fixation point moving up or down from the centre of the screen) and then make a valence judgement to a target word. Metaphoric congruency effect occurs when participants make faster judgements to the target with valence being matched with the prime ( good followed bright/top prime) than being mismatched with the prime ( good followed dark/bottom prime). In the present two experiments, we manipulated prime-target stimulus-onset asynchrony (SOA) and proportion of metaphorically congruent trials (congruency proportion) to tease apart the effects of automatic and controlled activation of brightness-valence and spatial-valence metaphoric associations on word valence judgements. Results showed an overall effect of congruency proportion on brightness-valence and spatial-valence metaphoric congruency effect, which was independent of prime-target SOA. The effect was enhanced or reversed when congruency proportion was higher or lower than 0.5, respectively, suggesting that the activation of metaphoric association could be modulated by strategic control. The implications of these findings on the Conceptual Metaphor Theory and semantic priming theories are discussed.